The Politics of Ritual Change : The zukru Festival in the Political History of Late Bronze Age Emar - Jr., John Tracy Thames,, (Harvard Semitic Monographs ;, 2020)
In The Politics of Ritual Change: The zukru Festival in the Political History of Late Bronze Age Emar, John Thames explores the intersection of ritual and politics in ancient Syria. The cuneiform texts describing an elaborate festival called zukru invite the reader to consider the development of the ritual as a result of political influence. This book suggests a new understanding of the relationship between the Hittite Empire and the city of Emar that is best observed through religious texts. The Harvard Semitic Monographs series publishes volumes from the Harvard Museum of the Ancient Near East. Other series offered by Brill that publish volumes from the Museum include Harvard Semitic Studies and Studies in the Archaeology and History of the Levant, https://hmane.harvard.edu/publications.